Pengaruh Model Pembelajaran Time Token Terhadap Motivasi Belajar Matematika Siswa kelas VII di SMPN 5 Mandau - Jannah, Raudatul; Medika , Gema Hista; Imamuddin, Imamuddin; Rahmat, Tasnim (Polinomial : Jurnal Pendidikan Matematika, 2025)
This study was conducted with the aim of examining whether the time token learning model affects the motivation to learn mathematics of class VII students at SMPN 5 Mandau during the 2023/2024 school year. This research is a quantitative study, using a Likert-scale questionnaire to collect numerical data and using the t-test to analyze the hypothesis statistically. The research design used is The Static Group Comparison Design. The population studied included all class VII students at SMPN 5 Mandau. Sampling was carried out randomly by applying normality checking techniques, homogeneity, and testing the comparison of the mean data from the group. The effect of the time token learning model on the motivation to learn mathematics was tested by making students in class VII-3 as the experimental class and class VII-1 as the control class. The instrument used to measure learning motivation was a motivation questionnaire. By utilizing SPSS Software for further analysis, it produced a significance value of 0.02 with a confidence level of 0.05, indicating that the significance value is smaller than ????. Based on the findings of this study, it is known that the application of the Time Token learning model has a significant impact in strengthening the motivation to learn mathematics for students in class VII of SMPN 5 Mandau.